2018
DOI: 10.1136/injuryprev-2017-042712
|View full text |Cite
|
Sign up to set email alerts
|

A social change perspective on injury prevention in China

Abstract: Economic and structural development and related social change in this period include: urbanisation, changes in demographics, life choices (eg, internal migration), education, poverty alleviation, health insurance and relevant regulations/legislation. These factors potentially explain much of the change in fatal injury rates in China. Data limitations persist. Increased investment in data and research would provide realistic opportunities for accelerated progress in implementing effective targeted interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Child injury is a significant global public health problem, and more than 98% of child injury deaths occur in developing countries [1]. Injuries mainly include road traffic injuries, suicide, falls, and drowningdrowning [2]. Life expectancy in developing countries is reduced by 1.19 years due to injury [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child injury is a significant global public health problem, and more than 98% of child injury deaths occur in developing countries [1]. Injuries mainly include road traffic injuries, suicide, falls, and drowningdrowning [2]. Life expectancy in developing countries is reduced by 1.19 years due to injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…In China [4], the proportion of injury deaths among 0-14 years of children in China rose from 18.69% in 2004 to 21.26% in 2011. Injury is also the leading cause of death among children aged 1 to 4 years old [2]. In China, 14.6% of deaths among children under 5 years of age are due to injuries [5].…”
Section: Introductionmentioning
confidence: 99%
“…No recent and comprehensive studies have been found, leaving a nearly decade-long gap in our understanding of the state of injury prevention in China. The rapid economic changes and increasing relevance of urban-rural disparities in the country highlight the need for a current understanding of injury-related deaths in children 18…”
Section: Introductionmentioning
confidence: 99%
“…Researchers noting the increase in injury deaths in Chinese cities during the latter half of the twentieth Century repeated without evidence the conventional wisdom that they are mainly the result of activities associated with rapid economic growth (Zhou 2012 ). From 2010 to 2015, however, injury death rates in Chinese cities were substantially lower than in the 1980s and 1990s while economic growth remained high (Ozanne-Smith and Li 2018 ).…”
Section: Introductionmentioning
confidence: 99%